A multilevel mixed effect analysis of neighbourhood and individual level determinants of risky sexual behaviour among young people in South Africa - Clifford Obby Odimegwu; Nebechukwu Henry Ugwu (Reproductive Health, 2022)
Plain language summary Risky sexual behaviour is most common among young people aged 15–24 years and is associated with an increase in sexually transmitted infections, including HIV/AIDS among this young productive age category. However, no adequate progress has been made in the reduction of these infectious diseases at the community level in South Africa. In this study, we investigate the effect of neighbourhood and individual-level factors leading to two measures of risky sexual behaviour; unprotected sex (non-condom use) and multiple sexual partnerships among young people. In this study, the target for young people in the South African context was because the country has a youthful population. Understanding the influence of neighbourhood and individual-level factors on the sexual behaviour of young people can help them live healthy as they transition to adulthood. We utilized cross-sectional data from the most recent South Africa Demographic and Health Survey, which was analyzed separately for males and females respectively, due to the cultural differences in sexual practices observed in many communities in South Africa. Our results confirmed an association between the neighbourhood and individual-level factors with youth engagement in risky sexual behaviour in South Africa. These results, imply that there is a need to review policies regarding the community-based interventions for sexual and reproductive health in other to reduce risky sexual behaviour among young people in South Africa.